Recovering Lost Local History: The Daily Record Project - Jeremy Hilburn; Tana Oliver; Leyna Varnum; Donyell L Roseboro (Middle Grades Review, 2019)
This practitioner perspective describes a collaboration between students and teachers at three middle schools, along with community partners, to recover and digitize news stories from The Daily Record, an African American owned newspaper that was attacked and burned in the 1898 Wilmington coup d’état.
Keywords: middle school; democracy in action; newspaper archives; displacement; Wilmington 1898